Impact of antithrombotic therapy resumption in patients with gastrointestinal bleeding: a multicenter retrospective cohort study - Ding Peng; Huihong Zhai (Therapeutic Advances in Gastroenterology)
Background: Gastrointestinal bleeding (GIB) is a critical clinical emergency associated with high morbidity and mortality. The widespread use of antithrombotic agents, including antiplatelet and anticoagulant medications, has increased the incidence of GIB. Objectives: Our study aims to address this gap by evaluating the impact of antithrombotic therapy on both 28-day mortality and rebleeding risk. Design: Retrospective cohort study using propensity score-based methods to address confounding. Methods: Data were extracted from three independent databases (MIMIC-IV, NWICU, and Xuanwu Hospital) spanning 2008–2022. inverse probability of treatment weighting (IPTW) was applied to balance baseline characteristics. Weighted logistic regression models assessed outcomes across antiplatelet, anticoagulant, and combination therapy subgroups. Results: After inverse probability of treatment weighting (IPTW) adjustment, the antithrombotic group maintained a significantly elevated rebleeding rate (19.9% vs 10.5%, p  < 0.001) and an increased risk of rebleeding (odds ratio (OR) = 2.118, 95% confidence interval (CI): 1.577–2.845, p  < 0.001). Conversely, the 28-day mortality was significantly lower in the antithrombotic group postadjustment (8.2% vs 12.5%, p  = 0.022; OR = 0.621, 95% CI: 0.412–0.935, p  = 0.023). Notably, early resumption of antithrombotic therapy (within 3 days) significantly increased the risk of mortality. Conclusion: Our study suggests that while antithrombotic therapy reduces 28-day mortality, it significantly increases rebleeding risk. Notably, the use of anticoagulants or combination therapy is linked to the highest rebleeding risk, compared to antiplatelets. Additionally, resuming antithrombotic therapy too early (i.e., within 3 days) may further elevate the risk of mortality.